A NUMERICAL ANALYSIS OF THE CORRELATION BETWEEN THE MECHANICAL BEHAVIOR OF BURIED PIPES AND THE RELATIVE STIFFNESS OF THE SOIL-PIPE SYSTEM (Revista Interdisciplinar de Pesquisa em Engenharia, 2018)
To avoid the economic and environmental lost caused by failing buried pipes, it is a must to predict the mechanical behaviour of the soil-pipe system. That is because different stiffness between the pipe and its surrounding soil leads to different deformations. The objective of this research is to correlate deformation and failure of buried pipes with the soilpipe relative stiffness. To achieve a reliable level of precision, a finite element methods analysis was carried out assisted by the software Abaqus. Different physical and mechanical parameters of both pipe and soil were tested on the FEM software in order to find the desired correlation. When discretizing the soil, an adaptive mesh was necessary. Thus, regions with differently sized elements were created where discontinuity was found to be high. By computing the results of this study, two points were observed. First, ratios of relative stiffness lesser than 1% have a failure controlled by the pipe since external forces are resisted by this structure. Second, a correlation between deformation/failure and relative stiffness of the system was established. Therefore, this research presents a simple and reliable approach in analyzing the failure mode of buried pipes.